2016
DOI: 10.1155/2016/6304163
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Properties of Alkaloid Extracts from Callistemon citrinus and Vernonia adoensis against Staphylococcus aureus and Pseudomonas aeruginosa

Abstract: The development of new antibiotics from new chemical entities is becoming more and more expensive, time-consuming, and compounded by emerging strains that are drug resistant. Alkaloids are plant secondary metabolites which have been shown to have potent pharmacological activities. The effect of alkaloids from Callistemon citrinus and Vernonia adoensis leaves on bacterial growth and efflux pump activity was evaluated on Staphylococcus aureus and Pseudomonas aeruginosa. At a concentration of 1.67 mg/mL, the alka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
74
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(80 citation statements)
references
References 19 publications
2
74
1
3
Order By: Relevance
“…In this study, the presence of alkaloids, phenolic acid, saponins, tannins, terpenoids and triterpenoids (table 1) suggests that the plant possess a unique antimicrobial range as these individual compounds exert action that thwarts the growth or development of disease causing pathogens [23]. Recent studies have shown that alkaloids, obtained from different plant extracts like Callistemon citrinus and Vernonia adoensis successfully diminished the growth of Staphylococcus aureus when compared to β-lactam antibiotics [24]. Bioactive compounds like tannins has also been studied and found to be active against Staphylococcus aureus alongside a host of bacterial pathogens linked with a variety of infections [25][26].…”
Section: Discussionmentioning
confidence: 89%
“…In this study, the presence of alkaloids, phenolic acid, saponins, tannins, terpenoids and triterpenoids (table 1) suggests that the plant possess a unique antimicrobial range as these individual compounds exert action that thwarts the growth or development of disease causing pathogens [23]. Recent studies have shown that alkaloids, obtained from different plant extracts like Callistemon citrinus and Vernonia adoensis successfully diminished the growth of Staphylococcus aureus when compared to β-lactam antibiotics [24]. Bioactive compounds like tannins has also been studied and found to be active against Staphylococcus aureus alongside a host of bacterial pathogens linked with a variety of infections [25][26].…”
Section: Discussionmentioning
confidence: 89%
“…The presence of alkaloids alone is highly suggestive of a broad antimicrobial spectrum as alkaloids are reportedly extensively used as pharmaceuticals, psycho-stimulants, narcotics and poisons due to their renowned biologic activities [48]. The activity of alkaloids have been investigated in plants like Callistemon citrinus and Vernonia adoensis whereby at concentrations of 1.7mg/ml, it inhibited the growth of Staphylococcus aureus with comparable effects to ampicillin [49]. Other possibilities include the synergies between phenolic acids and tannins, both of which have been studied and found to be active against Staphylococcus aureus alongside a host of bacterial pathogens linked with respiratory infections [50].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the availability of a wide range of antibiotics, microorganisms are constantly developing mechanisms of resistance to these agents (Mabhiza et al, 2016). Therefore, the increased microbial resistance leads to the development of new antimicrobial agents, such as molecules present in natural sources (Sassi et al, 2007).…”
Section: Introductionmentioning
confidence: 99%